Facilitated case conferences on end-of-life care for persons with advanced dementia—a qualitative study of interactions between long-term care clinicians and family members. (12th February 2022) - Francisco, Mari Claire; Lane, Heather; Luckett, Tim; Disalvo, Domenica; Pond, Dimity; Mitchell, Geoffrey; Chenoweth, Lynette; Phillips, Jane; Beattie, Elizabeth; Luscombe, Georgina; Goodall, Stephen; Agar, Meera
Abstract: Background: Prognostic uncertainty and the need for proxy decision-making owing to cognitive impairment in advanced dementia, adds complexity to end-of-life care planning within the long-term care setting. Case conferences provide a structure to facilitate difficult conversations and an opportunity for family and clinicians to engage in prospective planning, and reach agreement on goals of end-of-life care. Objective: To explore interactions between multidisciplinary healthcare clinicians and families during facilitated case conferences on end-of-life care for residents with advanced dementia. Methods: A qualitative approach was used. Transcripts of audio-recorded case conferences facilitated by a trained registered nurse were coded by two independent researchers and analysed inductively. Transcripts were selected from an available pool until thematic saturation was reached. Emerging themes were confirmed with the wider research group. Results: Thematic saturation was reached after 25 transcripts. An overarching theme concerned the ways in which clinicians and families bridged medical and person-centred perspectives. Subthemes included: details of day-to-day care versus establishing overall goals of care; expression of emotion versus retreat from emotion; and missed opportunities versus expressed cues. Successful facilitation served to 'bridge the gap' between family and clinicians. Conclusion: Facilitation of case conferences for residents with advanced dementia should focus on ensuring that: clinicians do not miss opportunities to discuss end-of-life care; discussions on the minutiae of care regularly return to the resident's broader goals of care; and information on dementia and treatments provided by clinicians is integrated with advice by family members regarding the resident's premorbid values and likely preferences.